Cold-Induced RNA-Binding Protein Promotes Glucose Metabolism and Reduces Apoptosis by Increasing AKT Phosphorylation in Mouse Skeletal Muscle Under Acute Cold Exposure - Liu, Yang; Liu, Peng; Hu, Yajie; Cao, Yu; Lu, Jingjing; Yang, Yuying; Lv, Hongming; Lian, Shuai; Xu, Bin; Li, Shize (Frontiers in Molecular Biosciences, 2021)
The main danger of cold stress to animals in cold regions is systemic metabolic changes and protein synthesis inhibition. Cold-induced RNA-binding protein is a cold shock protein that is rapidly up-regulated under cold stimulation in contrast to the inhibition of most proteins and participates in multiple cellular physiological activities by regulating targets. Therefore, this study was carried out to investigate the possible mechanism of CIRP-mediated glucose metabolism regulation and survival promotion in skeletal muscle after acute cold exposure. Skeletal muscle and serum from mice were obtained after 0, 2, 4 and 8 h of acute hypothermia exposure. Subsequently, the changes of CIRP, metabolism and apoptosis were examined. Acute cold exposure increased energy consumption, enhanced glycolysis, increased apoptosis, and up-regulated CIRP and phosphorylation of AKT. In addition, CIRP overexpression in C2C12 mouse myoblasts at each time point under 37°C and 32°C mild hypothermia increased AKT phosphorylation, enhanced glucose metabolism, and reduced apoptosis. CIRP knockdown by siRNA interference significantly reduced the AKT phosphorylation of C2C12 cells. Wortmannin inhibited the AKT phosphorylation of skeletal muscle after acute cold exposure, thereby inhibiting glucose metabolism and aggravating apoptosis. Taken together, acute cold exposure up-regulates CIRP in mouse skeletal muscle, which regulates glucose metabolism and maintains energy balance in skeletal muscle cells through the AKT signaling pathway, thus slowing down the apoptosis of skeletal muscle cells.